EKSPLORASI KESEJAHTERAAN PSIKOLOGIS INDIVIDU DEWASA AWAL PENYANDANG TUNANETRA - Harimukthi, Mega Tala; Dewi, Kartika Sari (Faculty of Psychology, Diponegoro University, 2014)
AbstractThis study aims to explore the psychological well-being of individuals who were blind in early adulthood (late blind), particularly to understand the changes and the antecedents of their psychological well-being. Two adults, aged 20-40 years, who were blind in early adulthood, had participated in this study. This is a qualitative phenomenological study. Data were analyzed using the interpretative phenomenological analysis (IPA). The results showed that late blind brought several impacts on subjects. Both subjects identified a decreased communication skill, a reduced movement ability, and negative emotional response in the beginning of blindness as the antecedents of their psychological well-being. The increased of psychological well-being was obtained due to social support -in terms of emotional, informational, and instrumental support- from family, partner, friends, and community. Although both subjects applied different coping strategies, they both reported an increased psychological well-being after they reached self-acceptance dimension. This study revealed selfacceptance as initial dimension that helped subjects to reach other dimensions of psychological well-being: life goals, independence, environment mastery, personal growth, and positive relationships with others.Â